NF-κB Mediates the Expression of TBX15 in Cancer Cells. - Jéssica Arribas; Tatiana Cajuso; Angela Rodio; Ricard Marcos; Antonio Leonardi; Antonia Velázquez (PLoS ONE, 2016)
TBX15 is a T-box transcription factor essential for development, also proposed as a marker in prostate cancer; and, recently, its antiapoptotic function indicates a role in carcinogenesis. Regulation of TBX15 is uncovered. In this study, we investigated the regulation of TBX15 expression in human cancer cells, by analyzing the regulatory function of a 5'-distal conserved region of TBX15. Bisulfite sequencing showed high methylation of the CpG island contained in this region that was not correlated with TBX15 mRNA levels, in the cancer cell lines analyzed; however, after 5-aza-dC treatment of TPC-1 cells an increase of TBX15 expression was observed. We also found a significant response of TBX15 to TNF-α activation of the NF-κB pathway using five cancer cell lines, and similar results were obtained when NF-κB was activated with PMA/ionomycin. Next, by luciferase reporter assays, we identified the TBX15 regulatory region containing two functional NF-κB binding sites with response to NF-κBp65, mapping on the -3302 and -3059 positions of the TBX15 gene. Moreover, a direct interaction of NF-κBp65 with one of the two NF-κB binding sites was indicated by ChIP assays. In summary, we provide novel data showing that NF-κB signaling up-regulates TBX15 expression in cancer cells. Furthermore, the link between TBX15 and NF-κB found in this study may be important to understand cancer and development processes.